Budgetpolitik im Zeitalter verminderter Erwartungen - Markus Marterbauer (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
– The concept of financial balances implies that the general government balance can be improved only if the enterprise sector and the foreign sector simultaneously increase their financial deficits and the household sector cuts its surplus. This paper explores how these adjustments can be influenced by economic policy during a period of diminished expectations (a period of weak GDP growth which is expected to persist for the coming years). Credit financed growth of private investment is unlikely to accelerate as capacity utilization rates are low. Increased spending by the foreign sector, which allows an export oriented growth strategy, could be dampened by simultaneous budget consolidation efforts of all European countries. Savings rates of private households have increased during the crisis. In order to reduce them various alternatives are discussed. Firstly, a credit financed housing bubble This has been practiced by some economies in recent years, but proved to be not sustainable. Secondly, a decline of unemployment rates and consequently of precautionary saving: During periods of low growth of GDP and employment, improvements in the employment elasticity of growth enhancing policy measures and reductions of working time could be effective in this respect. Thirdly, incentives for upper income households to expand investment expenditures and cut back their savings. Fourthly, a redistribution of wealth and income: This strategy leads to a decrease of average savings rates and an increase of consumption rates of private households.
urn:nbn:de:101:1-201101312844
Keywords: E21; E62; H30; H62; 330; Budget consolidation; fiscal balances; savings rates of private households; Haushaltsdefizit; Konjunktur; Haushaltskonsolidierung; Sparen; Außenwirtschaftliches Gleichgewicht; Leistungsbilanz; Österreich